Demographic modeling to fine‐tune conservation targets: importance of pre‐adults for the decline of an endangered raptor. Issue 3 (19th January 2021) - Sergio, Fabrizio; Tavecchia, Giacomo; Blas, Julio; Tanferna, Alessandro; Hiraldo, Fernando
Abstract: Large, long‐lived species with slow life histories and protracted pre‐breeding stages are particularly susceptible to declines and extinction, often for unknown causes. Here, we show how demographic modeling of a medium‐sized raptor, the Red Kite Milvus milvus, can aid to refocus conservation research and attention on the most likely mechanisms driving its decline. Red Kites' survival and reproduction increased through three sequential stages for 1–2, 3–6, and 7–30 yr of age, mainly corresponding to individuals that are dispersing, attempting to gain a territory, and breeding. As typical of long‐lived species, elasticities were highest for adult (≥7 yr old) survival, but this was high, with little scope for improvement. Instead, the declines were driven by an extremely low survival of pre‐adults in their first years of life, which weakened the whole demographic system by nullifying the offspring contribution of adults and curtailing their replacement by recruits. For example, 27 pairs were necessary to generate a single prime age adult. Simulation of management scenarios suggested that the decline could be halted most parsimoniously by increasing pre‐adult survival to the mean levels recorded for other areas, while only the synergistic, simultaneous improvement of breeding success, adult and pre‐adult survival could generate a recovery. We propose three actions to attain such goals through selective supplementary feeding of both breeding and non‐breeding individuals, and through mortality improvement by GPS remote‐sensing devices employed as surveillance monitoring tools. Our results show how improving demographic models by using real, local vital rates rather than "best guess" vital rates can dramatically improve model realism by refocusing attention on the actual stages and mortality causes in need of manipulation, thus building precious time and resources for conservation management. These results also highlight the frequent key role of pre‐adult survival for the management of long‐lived species, coherent with the idea of demographic systems as integrated chains only as strong as their weakest link.